2017
DOI: 10.1016/j.fsigen.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic discrimination of identical twins from blood under the forensic scenario

Abstract: Monozygotic (MZ) twins share the same STR profile, demonstrating a practical problem in forensic casework. DNA methylation has provided a suitable resource for MZ twin differentiation; however, studies addressing the forensic feasibility are lacking. Here, we investigated epigenetic MZ twin differentiation from blood under the forensic scenario comprising i) the discovery of candidate markers in reference-type blood DNA via genome-wide analysis, ii) the technical validation of candidate markers in reference-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 49 publications
2
31
1
4
Order By: Relevance
“…Although some studies have explored the value of epigenetic profiling in forensically discriminating MZ twins [ 62 , 63 ], it is not yet fully established whether the observed twin-to-twin differences are twin pair-specific, or might be universal and applicable across twin pairs, as would be preferred. Recently, a first attempt was made to demonstrate the feasibility of differentiating between MZ twins using forensic epigenetics [ 15 ]. This study showed that most, but not all, twin-differentiating CpG sites (which were identified using genome-wide screening technologies in reference-type blood DNA) could be replicated by targeted methods that are suitable for forensics in trace-type DNA from bloodstains, highlighting technical challenges [ 15 ].…”
Section: Current Progress In Forensic Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have explored the value of epigenetic profiling in forensically discriminating MZ twins [ 62 , 63 ], it is not yet fully established whether the observed twin-to-twin differences are twin pair-specific, or might be universal and applicable across twin pairs, as would be preferred. Recently, a first attempt was made to demonstrate the feasibility of differentiating between MZ twins using forensic epigenetics [ 15 ]. This study showed that most, but not all, twin-differentiating CpG sites (which were identified using genome-wide screening technologies in reference-type blood DNA) could be replicated by targeted methods that are suitable for forensics in trace-type DNA from bloodstains, highlighting technical challenges [ 15 ].…”
Section: Current Progress In Forensic Epigeneticsmentioning
confidence: 99%
“…Currently, only a limited number of DNA methylation markers are applied for a few forensic purposes, using technologies that enable the analysis of a small number of such markers. These approaches can be classified as forensic epigenetics, and include DNA methylation profiling for tissue determination [ 13 ], age prediction [ 14 ], and differentiation between monozygotic twins [ 15 ]. The concept of personalized epigenomics, which is already used in medical research [ 16 ], has not yet been recognized in the forensic field.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not always effective in analyzing samples in regular criminal or paternity testing cases. Small genetic or epigenetic differences have been identified for distinguishing between MZ twins [2][3][4][5]. Additionally, extremely rare mutations in the nuclear genome, identified by whole-genome sequencing (WGS), were useful in distinguishing between identical twins in paternity testing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate DNA typing results are nowadays the basis of increasing number of judicial decisions (Vidaki et al, 2017). Still, the main limitation in forensic genetics involves distinguishing individuals within a pair of monozygotic twins in criminal or paternity cases (Stewart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This scenario poses an urgent challenge to forensic genetics especially that monozygotic twinning accounts for 1 in 250 live births on average (Fraga et al, 2005). Till the present day, and despite the high power of discrimination that characterizes the well identified 16 to 24 autosomal short tandem repeat (STR) markers, monozygotic twins discrimination is still limited in forensics (Xu et al, 2015;Vidaki et al, 2017). Furthermore, lineage markers are in general less informative than autosomal ones.…”
Section: Introductionmentioning
confidence: 99%